2022
DOI: 10.1029/2021jc017625
|View full text |Cite
|
Sign up to set email alerts
|

Peak Water Level Response to Channel Deepening Depends on Interaction Between Tides and the River Flow

Abstract: The Pearl River Delta represents a tide‐influenced lowland delta where sand mining has deepened the distributary channels. This study sets out to investigate the impacts of channel deepening on peak water levels across the delta. Based on collected hydrological data before and after sediment mining and hydrodynamic modeling, three regions are identified where sand mining‐induced changes in peak water levels have a different underlying cause. In the river‐dominated regions, peak water levels have significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…A similar effect was found for the Blyth estuary (Suffolk, eastern England) (French, 2008), and a simplified analysis of 36 estuaries worldwide confirms that this effect predominantly holds for relatively deep estuaries and deltaic channels (Leuven et al., 2019). This implies that the fate of shallow deltaic channels is probably very different, because they have not yet experienced the same degree of urbanization and deepening as for example, the RMD, the Pearl Delta (Bao et al., 2022) and the Yangtze Delta (Chen et al., 2016; Zhang et al., 2019).…”
Section: Discussion and Implications For Sustainable Management Of De...mentioning
confidence: 99%
See 3 more Smart Citations
“…A similar effect was found for the Blyth estuary (Suffolk, eastern England) (French, 2008), and a simplified analysis of 36 estuaries worldwide confirms that this effect predominantly holds for relatively deep estuaries and deltaic channels (Leuven et al., 2019). This implies that the fate of shallow deltaic channels is probably very different, because they have not yet experienced the same degree of urbanization and deepening as for example, the RMD, the Pearl Delta (Bao et al., 2022) and the Yangtze Delta (Chen et al., 2016; Zhang et al., 2019).…”
Section: Discussion and Implications For Sustainable Management Of De...mentioning
confidence: 99%
“…Observations from individual estuaries have indicated that dredging can decrease channel roughness, increase tidal amplitudes, enhance depth convergence, decrease flood wave attenuation and reduce tidal dampening and storm surge dampening (Familkhalili et al., 2020; Muñoz et al., 2022; Talke et al., 2021; Talke & Jay, 2020). Capturing this behavior in modeling has proved challenging (Cai et al., 2012), particularly when estuaries are heavily anthropogenically influenced, and move away from classic, width converging estuary morphology, such as in the Rhine‐Meuse Delta (RMD) in The Netherlands (Cox, Lingbeek, et al., 2022) and the Pearl Delta in China (Bao et al., 2022). With channel deepening, the tidal range generally increases and storm surge waves also amplify, while high river discharge events generally exert a smaller control on peak water levels in the delta channels (Talke et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations